The border between progenitor cell recruitment and nephron shaping in the fetal human kidney during late gestation: a basic but understudied region - Minuth, Will W. (Frontiers in Nephrology, 2026)
IntroductionThe last 3 months of pregnancy are formative for the development of the fetal human kidney. Clinical experience with preterm and low birth weight infants indicates particular vulnerability during this period, as different noxae can terminate the development of new nephrons. This leads to oligonephropathy, which is associated with serious health consequences later in life. While the clinical aspects have been intensely investigated, few data point to the traces left by these noxae. In the nephrogenic zone, a reduction in its width and the absence of S-shaped bodies have been reported.PurposeNot only the targets of noxae but also the site and early links of nephron formation remain poorly investigated. This concerns the individual compartments of the nephrogenic zone and the border between the district of progenitor cell recruitment (DPCR) and the area of nephron shaping (ANS) as a potential target of noxae.MethodsTo shed initial light on this issue, the border between the DPCR and ANS was recorded using microanatomical criteria.ResultsNephron morphogenesis is shown to start at the far end of a cap mesenchyme, with the condensate opposite the head of a collecting duct (CD) ampulla still located within the DPCR. Driven by the mesenchymal-to-epithelial transition, the pretubular aggregate also arises at this site. Its proximal end remains adjacent to the connecting tubule of a previously formed nephron. Subsequently, it converts into the primitive renal vesicle, which thereafter expands within the ANS. Although separation is incomplete, the medial part of the distal pole adheres to the CD ampulla at the section border between its head and conus. This linkage of the future connecting tubule suggests that the conus of the CD ampulla co-elongates with the medial aspect of the shaping nephron stages.ConclusionsClosely related key points during early nephron formation are identified. Damage to only one of these points may result in either developmental arrest. Knowledge of these structural details is vital for pathological screening, interpretation of cell biological labeling, and identification of imprints left by noxae.